2015
DOI: 10.1371/journal.pone.0145229
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Alterations in Perirenal Adipose Tissue Transcriptomic Networks with Cessation of Voluntary Running

Abstract: In maturing rats, the growth of abdominal fat is attenuated by voluntary wheel running. After the cessation of running by wheel locking, a rapid increase in adipose tissue growth to a size that is similar to rats that have never run (i.e. catch-up growth) has been previously reported by our lab. In contrast, diet-induced increases in adiposity have a slower onset with relatively delayed transcriptomic responses. The purpose of the present study was to identify molecular pathways associated with the rapid incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…This suggests that the acute change in systemic inflammation did not contribute to the insulin resistance in the placebo post-WL group and that CRP levels are not tightly linked with 11␤-HSD1 expression in the epididymal fat pad. However, it was recently found that in wheel-locked rats there is an upregulation of gene transcripts related to immunity, macrophage infiltration, and proinflammation within perirenal adipose tissue (68). Thus, there may be local inflammatory changes in adipose tissue that play a key role in impaired metabolic health in the animals post-wheel lock.…”
Section: Insulin Resistance After Daily Exercise and Cr Is Stoppedmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the acute change in systemic inflammation did not contribute to the insulin resistance in the placebo post-WL group and that CRP levels are not tightly linked with 11␤-HSD1 expression in the epididymal fat pad. However, it was recently found that in wheel-locked rats there is an upregulation of gene transcripts related to immunity, macrophage infiltration, and proinflammation within perirenal adipose tissue (68). Thus, there may be local inflammatory changes in adipose tissue that play a key role in impaired metabolic health in the animals post-wheel lock.…”
Section: Insulin Resistance After Daily Exercise and Cr Is Stoppedmentioning
confidence: 99%
“…Considering the link between adipose tissue inflammation, elevated 11␤-HSD1, and a recent study that demonstrated an upregulation of adipose proinflammatory gene transcripts following wheel lock in rats (68), future studies should explore whether a key protective mechanism of mifepristone is through reducing local inflammatory markers such as TNF␣, IL-6, and NF-B or by limiting macrophage infiltration. Conversely, it would be interesting to determine whether administration of an anti-inflammatory compound would yield similar metabolic benefits following wheel lock.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…; Ruegsegger et al . ), to levels comparable to those of rats with continuous wheel access. Additionally, we assessed mRNA expression in omental (OMAT) and subcutaneous adipose tissue (SAT) associated with hypoxia ( Vegf , Hif1α ), cell proliferation and differentiation ( Cdk2 , cyclin A1, cyclin D1) and metabolism (adiponectin, leptin), as well as energy homeostasis‐regulating mRNAs in the hypothalamus ( Pomc , Cart , Agrp , Npy , Lepr ).…”
Section: Introductionmentioning
confidence: 66%
“…; Ruegsegger et al . ), highlighting the importance of energy expenditure on adipocyte expansion during endurance types of exercise. Consistent with lack of change in food intake, we did not find differences in appetite control mRNAs in the Arc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation